GAPS IN THE MANAGEMENT OF TYPE 2 DIABETES MELLITUS AMONG WOMEN LIVING WITH HIV IN AN ACADEMIC MEDICAL CENTRE - Kukreja, Anjanna; Salleh, Anisa; Zakria, Muhammad Amir Haziq Bin (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION Type 2 Diabetes Mellitus (T2DM) poses significant cardiovascular risks. Individuals with HIV face compounded risks due to accelerated aging, chronic inflammation and certain antiretroviral therapies (ART). Postmenopausal women have increased cardiovascular risk. However, data on women living with HIV (WWH) and T2DM in Malaysia is scarce. METHODOLOGY This study examines gaps in the management of T2DM and cardiometabolic health among WWH undergoing routine HIV care in a tertiary hospital. We reviewed the electronic medical records of WWH with T2DM attending the Infectious Diseases (ID) Clinic at Universiti Malaya Medical Centre (UMMC) in 2023. We extracted HIV demographics, anthropometrics, latest HbA1c, fasting plasma glucose (FPG) and lipid levels, and defined targets for control as per the 6th Malaysian Clinical Practice Guidelines for T2DM. Gaps in care were defined as the proportion not achieving targets for control of metabolic parameters. RESULTS We collected data from 33 WWH with T2DM, representing 17.8% of all WWH in ID UMMC. Their median age was 54 years (IQR 49, 61) and the median duration since HIV diagnosis was 19 years (IQR 14, 25). All were on ART, with 30 (90.9%) having suppressed viral loads. Menopause status was recorded in 57.6% (n=19), with 78.9% (n=15) being menopausal. Four (12.1%) were active smokers. For T2DM management, 26 (96.3%) were on oral antidiabetic drugs (OADs) and 1 (3.7%) was on insulin. The most used OADs were metformin (65.7%), followed by sulfonylurea (25.7%) and SGLT2i (2.9%). Overall, 60.6% (n = 33) met the HbA1c target of <7% and 66.7% had an FPG within 4.4-7.0 mmol/L (n = 30/33). For lipids, 54.8% (n = 31/33) had triglycerides ≤1.7 mmol/L, 67.7% (n=31/33) HDL >1.2 mmol/L, and 56.7% (n = 30/33) LDL ≤2.6 mmol/L. 72.7% were on statins. For BP, only one (0.03%) had readings within the target range. 36.4% were on an ACE inhibitor or angiotensin-receptor blocker. Only 33.4% had an ideal BMI. CONCLUSION There are significant gaps in managing T2D among WWH. Addressing these gaps requires interdisciplinary collaboration for integrated care solutions.